AFFINE-INVARIANT FOURIER DESCRIPTORS AND THEIR APPLICATION IN A NUMBER PLATE RECOGNIZING SYSTEM - Nguyen Thanh Hai; Pham The Long; Nguyen Cong Dinh (Universitas Gadjah Mada, 2008)
This paper introduces a method for describing partial shapes that are affine-invariant. The proposed method facilitates the extraction of descriptors, which is effective for opened-curves and invariant to different viewpoints. This method helps to improve the performance and quality of real world object image recognizing systems. The proposed method was tested in a number plate recognition system.